Strategi Adaptasi Petani Minyak Putih Memanfaatkan Jejaring Sosial dan Kebiasaan Makan dalam Situasi Pandemi Covid-19 - M Chairul Basrun Umanailo (Universitas Medan Area, 2023)
Eucalyptus oil is highly sought after because of its antiseptic, antibacterial, and antifungal characteristics. It is marketed as a high-quality supplement because it is taken from eucalyptus trees. Even though there are plenty of resources to help farmers improve their lot in life, many are still struggling to make ends meet. This research aims to understand better how eucalyptus oil growers use their social networks and dietary habits to get by daily. This study adopts a phenomenological approach, which is a qualitative research methodology. Relevant notes, interviews, and literature reviews were used to compile the data. According to the study, the pandemic has restricted employment opportunities, prompting eucalyptus oil farmers to become “innovators” by selling oil directly to customers without going via a mutually agreed upon procedure. When people invest time and energy into developing meaningful relationships with one another, it usually pays off in the form of long-lasting and stable social institutions. Eating habits have become influenced by subjective attitudes and conventions and the adaptation patterns carried out by eucalyptus oil producers in coping with conditions during a pandemic.